Susceptibility of Enamel Treated with Bleaching Agents to Mineral Loss after Cariogenic Challenge - Hüseyin Tezel; Cigdem Atalayin; Ozlem Erturk; Ercument Karasulu (International Journal of Dentistry)
Objectives. Controversial reports exist whether bleaching agents cause a susceptibility to demineralization. The aim of this study was to compare the calcium loss of enamel treated with different bleaching agents and activation methods. Method and Materials. The specimens obtained from human premolars were treated in accordance with manufacturer protocols; 10% carbamide peroxide, 38% hydrogen peroxide light-activated, 38% hydrogen peroxide laser-activated, and no treatment (control). After cariogenic challenge calcium concentrations were determined by Inductively Coupled Plasma Mass Spectrometry. Results. No differences were found between the calcium loss of the laser-activated group and 10% carbamide peroxide group (𝑝>0.05). However, the differences between laser-activated and control groups were statistically significant (𝑝<0.05). The differences between 10% carbamide peroxide and the control group were not significant (𝑝>0.05). On the other hand, the light-activated group showed a significantly higher calcium loss compared with the other groups (𝑝<0.05). Conclusions. The results show that bleaching agents may cause calcium loss but it seems to be a negligible quantity for clinical aspects.